AN OVERVIEW OF REASONING ABILITY IN MATHEMATICS AND MATHEMATICS ACHIEVEMENT OF STUDENTS IN TERTIARY INSTITUTION - Onoshakpokaiye, Odiri E. (IJIET (International Journal of Indonesian Education and Teaching), 2023)
The study's goal is to assess students who are enrolled in postsecondary mathematics in terms of their achievement and mathematical reasoning skills. Most experts think that for students to study mathematics, they must possess the ability to reason since solving problems in mathematics demands it. The achievement has a bearing on this since it is important for the school and the instructors to be aware of the academic performance of the pupils in various subject areas to track their progress. A student's accomplishments aid the instructor in determining their rank. The idea that mathematics is the most difficult subject has made learning the subject quite challenging. The ability of mathematics to reason is one significant component of mathematics that many overlook. Mathematical reasoning is crucial for success in the sciences, humanities, and other fields that rely on it. The current study examined math achievement and thinking skills. 228 students served as the study sample for this investigation. The design is expo facto. To direct the study, two research questions were established. According to the study, students' achievement is influenced by mathematical thinking. Additionally, female students outperform male students in math and courses closely related to mathematics.